KAJIAN PERAN KELEMBAGAAN KELOMPOK TANI DALAM MENDAPATKAN MODAL USAHA AGRIBISNIS BAWANG MERAH - Sukadi, Sukadi (Jurnal Ilmu-Ilmu Pertanian, 2007)
The study aimed to understand the role of farmer groups to fasilitate and mediate their members, and collaborate with others, to access the agribusiness cost. Theirs study based on agro-ecosystem analysis in Tirtoharjo Village, Kretek Sub Regency, Bantul Regency on 2007.